I-V Characteristics of GaAs/AlAs Asymmetric Spacer Layer Tunnel Diode (ASPAT) Using Statistical Validation - E. Jamil; N. A. AzizulRahman; M. Othman; S. A. Rahman; Wan Zakiah Wan Ismail; K. N. Z. Ariffin (Penerbit UTHM, 2025)
Index by MyCite (Tier 3)